2013
DOI: 10.1136/oemed-2013-101717.270
|View full text |Cite
|
Sign up to set email alerts
|

270 Health and safety experience of commercial janitors

Abstract: Conclusions This analysis indicates that PI is a valid and reliable instrument which can be effectively used to monitor safety conditions at workplaces. Commercial janitors are an important group of low wage, largely immigrant workers who face significant potential risks at work, and yet have only been minimally studied for occupational injury and illness. Anecdotal reports from a local union representing commercial janitors in the Seattle area suggest pressures on the industry have produced a dramatic increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
0
9
1
Order By: Relevance
“…Due to different study methods and populations, it is difficult to compare these results to other studies. However, a previous study of janitors in Washington State assessed a change in work intensity, and found that among union janitors, reported work intensity increased by 8.6% over the 3‐year period between 2010 and 2013 . The current study did not measure the percent increase in workload, but did conclude that, among those who reported an increase in workload, 22% was attributable to intensity of work.…”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations
“…Due to different study methods and populations, it is difficult to compare these results to other studies. However, a previous study of janitors in Washington State assessed a change in work intensity, and found that among union janitors, reported work intensity increased by 8.6% over the 3‐year period between 2010 and 2013 . The current study did not measure the percent increase in workload, but did conclude that, among those who reported an increase in workload, 22% was attributable to intensity of work.…”
Section: Discussioncontrasting
confidence: 62%
“…Short sleep duration and poor quality of sleep are both risk factors for occupational injury . Previous research of SEIU janitors reported their having low sleep quality and getting less than 6 h of sleep per night . In the current study, adjusted analyses indicated an increased risk of injury for those who slept less than 6 h, compared to 8 or more hours, and for those who reported moderate to severe sleep disturbance compared to none or slight.…”
Section: Discussionmentioning
confidence: 38%
See 2 more Smart Citations
“…The expansion in commercial office space in WA has outpaced the growth of the workforce and may increase work demands. 41 Janitors have recently reported increasing workloads 42 , 43 , 44 which may put them at increased risk of work‐related injuries.…”
Section: Introductionmentioning
confidence: 99%